Parasitism of the nasal mite Sternostoma tracheacolum Lawrence, 1948 (Mesostigmata: Rhinonyssidae) in captive birds in Brazil - Bassini-silva, Ricardo; Jacinavicius, Fernando De Castro; Pereira, Josivania Soares; Werther, Karin; Spicer, Greg Sherwood; Barros-battesti, Darci Moraes [UNESP] (Colégio Brasileiro de Parasitologia Veterinária, 2019)
Abstract Nasal mites (Mesostigmata: Rhinonyssidae) are obligatory endoparasites of birds, and the resulting parasitism can be harmful to the host’s respiratory system. The nasal mite Sternostoma tracheacolum Lawrence has caused significant respiratory issues, including serious injuries that possibly cause death of the host. In this study, we report two cases of captive birds parasitized by S. tracheacolum. The first case is a histopathological description of S. tracheacolum parasitizing the Gouldian Finch (Chloebia gouldiae) in the southeast region of Brazil, that showed partially or totally absence of the characteristic respiratory epithelium in trachea lumen. The other describes, for the first time, the parasitism of this species in a canary (Serinus canaria) in the northeast region of the country.

Resumo Os ácaros nasais (Mesostigmata: Rhinonyssidae) são endoparasitos obrigatórios das aves, e este parasitismo pode ser prejudicial ao sistema respiratório de seu hospedeiro. A espécie de ácaro nasal Sternostoma tracheacolum Lawrence tem causado importantes problemas respiratórios, incluindo lesões graves que possivelmente causam a morte do hospedeiro. Neste estudo, relatamos dois casos de aves em cativeiro parasitadas por S. tracheacolum. O primeiro caso é uma descrição histopatológica de S. tracheacolum parasitando um Diamante-de-gould (Chloebia gouldiae) na região sudeste do Brasil, mostrando parcial ou total ausência do epitélio respiratório característico do lúmen da traqueia. O outro descreve, pela primeira vez, o parasitismo desta espécie em um canário (Serinus canaria) na região nordeste do país.
Parasitismo do ácaro nasal Sternostoma tracheacolum Lawrence, 1948 (Mesostigmata: Rhinonyssidae) em aves de cativeiro no Brasil
Keywords: Sternostoma tracheacolum; endoparasite; Chloebia gouldiae; Serinus canaria; Sternostoma tracheacolum; endoparasita; Chloebia gouldiae; Serinus canaria